User Interface and RF-Front End Design for Radio Direction Finding-Miniature Unmanned Air Vehicles (RDF-MUAV) - Ibrahim, Nurul Saliha Amani; Chong, Bor Sheng; Saparudin, Faiz Asraf; A. Majid, Huda (WARSE, 2020)
Radio direction finding perform better at high altitude due to greater line of sight coverage. In this paper, the radio direction finding-miniature unmanned air vehicles (RDF-MUAVs) platform able to localize the beacon by accessing the direction of signal and report it back to the ground station immediately, improving search and rescue operations. RDF-MUAV system divided into four major part; RF front end design; RF software design; ground station design; and user interface (UI). This paper focuses on two out of the four major parts, which designing a good UI and RF front end to be integrated into the system. The UI is designed using Linux, Apache, MySQL, PHP (LAMP) architecture in Raspberry Pi platform that can display accurate data obtained from RDF-MUAVs. The UI is based on HTML which is lightweight, modifiable and can be accessed through smartphone, tablets, or personal computer. In the antenna design, phase direction finder method is chosen. The rotation of antenna can be done by moving the UAV to obtain the bearing to the source signal. Proposed type of antenna is Yagi-Uda antenna due to its high gain and relatively small size. The folded dipole is chosen as the driven element of the antenna due to its bandwidth characteristics and directivity. Result shows the function-al bandwidth is 200MHz which can accept electromagnetic waves from 500MHz to 600MHz and 900MHz to 1000MHz. Overall, the design implementations provide a feasible system in search and rescue operation.